Comparative Study of Short-Term Outcome of Live Related Renal Transplantation From Grafts Having Single vs Multiple Arteries - Rashid, Harun Or; Islam, AKM Anwarul; Alam, AKM Khursidul; Hasan, Md Sajid; Dulal, Md Habibur Rahman (Bangladesh Journal of Urology, 2020)
Objective: To compare the outcome of live related renal transplantation between the Grafts having single vs multiple arteries. Materials and Methods: The data of 94 renal transplants with single and multiple arteries performed between January 2011 and December 2012 were collected from Bangabandhu Sheikh Mujib Medical University and National Kidney Foundation. Sixty three renal transplants with single renal artery were compared to 31 transplants with multiple arteries. The aspects analyzed were number of arteries of the graft, donor type, ischemia time, time spent for arterial anastomosis, time spent for total vascular anastomosis and time for whole operation, vascular reconstruction technique, the occurrence of surgical complications, the incidence of delayed graft function, graft function 6 month after transplantation, graft loss and mortality. Results: The incidence of surgical complications in grafts with single artery and multiple renal artery was respectively: vascular 6.4% and 3.2%; urological 13.2% and 9.6%, other surgical complications was 3,2% and 3.2%, and the difference were not significant among the two groups. Symptomatic lymphocele was 3.2% observed in single artery group but the incidence of lymphoceles was 6.4% in grafts with multiple arteries (p < 0.005). The incidence of delayed graft function in grafts with a single artery and multiple arteries was respectively 6.4% and 6.4% (p =<0.005). Mean serum creatinine at the end of 6th months of postoperative period was 1.33mg/dl and 1.67 mg/dl in grafts with single and multiple arteries respectively (p<0.005). Cold ischemia time, preparation time duration of in vivo arterial anastomosis and the total length of operation time was significantly longer in the multiple artery group(p<0.005). Six months grafts survival in single and multiple artery was 88.9% and 87.1% respectively. Conclusions: Kidney transplantation using grafts having single and multiple arteries present similar indeces of surgical complications and short-term outcome. Though, lymphoceles was more frequent among grafts with multiple arteries but the difference were not significant among the two groups. In other words. Live related renal transplantation from grafts having multiple arteries is safe and has a good outcome. Bangladesh Journal of Urology, Vol. 17, No. 1, Jan 2014 p.9-16